Psychometric evaluation of the healthy aging activity engagement scale - Tingting Lu; Linghui Kong; Huijun Zhang (Frontiers Media S.A., 2022)
ObjectiveThe aim of this study was to translate the Healthy Aging Activity Engagement Scale (HAAE) into Chinese and validate its psychometric properties in the middle-aged and elderly population.MethodsA total of 424 middle-aged and elderly people were recruited from China's Jiangsu Province, Liaoning Province, Shandong Province, and Heilongjiang Province. Cronbach's α co-efficient, split-half reliability, and test-retest reliability were used to evaluate the reliability of the translated scale. Expert consultation was used to evaluate the content validity of the translated scale. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to evaluate the structural validity of the scale.ResultsThe Cronbach's α co-efficient of the Chinese version of HAAE was 0.965 and the Cronbach's α co-efficient of the dimensions ranged from 0.898 to 0.957. The split-half reliability was 0.807, and the test-retest reliability was 0.850. The content validity index of the scale (S-CVI) was 0.969. A total of three common factors were extracted from the EFA. The CFA validated the explored 3-factor structure, and the indicators were fitted well (χ2/df = 1.393, comparative fit index = 0.982, goodness- of- fit index = 0.911. Tucker-Lewis Index = 0.981 and root mean square error of approximation = 0.030).ConclusionThe translated Chinese version of HAAE had suitable reliability and validity in the middle-aged and elderly population. The translated scale will be used to evaluate the level of healthy aging among middle-aged and elderly people in Chinese mainland. Furthermore, it also can provide some health advice for clinical patients.